A comprehensive investigation of the impacts of discovery time and fire brigade response time on life safety and property protection in England. Issue 1 (January 2023) - Manes, Martina; Rush, David
The investigation of fire incidents in buildings is essential in understanding the consequences on occupants and property. Moreover, a fundamental role in life safety and property protection is represented by the minutes after the fire ignition. Therefore, it is possible to evaluate the effects that the discovery time of occupants and response time of the fire brigades have on a successful evacuation, reduction of fatalities and fire confinement in buildings. The Dwellings and Other buildings fire statistical databases published by the Home Office in England with data from 2010/11 to 2016/17 are investigated to determine how the fatality/casualty rates vary with different discovery times in Dwellings according to the methodology provided by Ramachandran, and adopted in the PD 7974-7:2003. Furthermore, the average response time of the fire brigades for Dwellings and Other buildings appears to be between 7-8 and 8-9 minutes, respectively. When the response times are analyzed in terms of the fatality/casualty rate, there is an upward trend in Other buildings . Finally, response time is also examined considering fire spread, fire and total damage showing that in Other buildings the classes of more severe fire damage increase for a response time between 6 and 8 minutes.